EVALUASI PENYELENGGARAAN PENDIDIKAN INKLUSI BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SDN 131/IV KOTA JAMBI - Isabella, Paramita; Emosda, Emosda; Suratno, Suratno (Program Magister Teknologi Pendidikan Universitas Jambi, 2014)
The research was aimed to evaluate the implementation of inclusive education in SD Negeri 131/IV Kota Jambi using CIPP (context, input, process, and product) models. This research is a qualitative study with case study approach. Data was collected through observation, interviews, and documentary study. Data analysis was conducted in three phases: the first phase was preliminary analysis, the second phase was done while collecting data at the site, and the third one was done after completing the data collection. The data analysis was conducted through developing categories, data reduction, data presentation, making conclusions, and verification. The study concludes that the implementation of inclusive education in Elementary School of 131/IV Jambi City generally classified as good criteria where there are 68.35 % of sub-indicators of inclusive education’s implementation at school that appropriate with the standards. Inclusive education at school provides benefits, but there are some parts of supporting programs that have not been accordance with the standards. Therefore, the researcher recommends that the program can be continued, with the term revisions must be made through an adjustment and improvement of some components that have not been appropriate to these provisions to get a better quality of the program. Furthermore, for others that would like to conduct similar studies in different settings should be able to avoid what the limitations of this study, namely by narrow the focus of research and using mix-method research. Keyword: evaluation, inclusive education